Identification and Analysis of bZIP Family Genes in Sedum plumbizincicola and Their Potential Roles in Response to Cadmium Stress - Lu, Zhuchou; Qiu, Wenmin; Jin, Kangming; Yu, Miao; Han, Xiaojiao; He, Xiaoyang; Wu, Longhua; Wu, Chao; Zhuo, Renyin (Frontiers in Plant Science, 2022)
Sedum plumbizincicola (Crassulaceae), a cadmium (Cd)/zinc (Zn)/lead (Pb) hyperaccumulator native to Southeast China, is potentially useful for the phytoremediation of heavy metal-contaminated soil. Basic leucine zipper (bZIP) transcription factors play vital roles in plant growth, development, and abiotic stress responses. However, there has been minimal research on the effects of Cd stress on the bZIP gene family in S. plumbizincicola. In this study, 92 SpbZIP genes were identified in the S. plumbizincicola genome and then classified into 12 subgroups according to their similarity to bZIP genes in Arabidopsis. Gene structure and conserved motif analyses showed that SpbZIP genes within the same subgroup shared similar intron–exon structures and motif compositions. In total, eight pairs of segmentally duplicated SpbZIP genes were identified, but there were no tandemly duplicated SpbZIP genes. Additionally, the duplicated SpbZIP genes were mainly under purifying selection pressure. Hormone-responsive, abiotic and biotic stress-responsive, and plant development-related cis-acting elements were detected in the SpbZIP promoter sequences. Expression profiles derived from RNA-seq and quantitative real-time PCR analyses indicated that the expression levels of most SpbZIP genes were upregulated under Cd stress conditions. Furthermore, a gene co-expression network analysis revealed that most edge genes regulated by hub genes were related to metal transport, responses to stimuli, and transcriptional regulation. Because its expression was significantly upregulated by Cd stress, the hub gene SpbZIP60 was selected for a functional characterization to elucidate its role in the root response to Cd stress. In a transient gene expression analysis involving Nicotiana benthamiana leaves, SpbZIP60 was localized in the nucleus. The overexpression of SpbZIP60 enhanced the Cd tolerance of transgenic Arabidopsis plants by inhibiting ROS accumulation, protecting the photosynthetic apparatus, and decreasing the Cd content. These findings may provide insights into the potential roles of the bZIP family genes during the S. plumbizincicola response to Cd stress.